2021
DOI: 10.1186/s12880-021-00557-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of CBCT versus intraoral imaging for assessment of peri‐implant bone defects

Abstract: Background Early detection of marginal bone loss is vital for treatment planning and prognosis of teeth and implant. This study was conducted to assess diagnostic accuracy of CBCT compared to intra-oral (IO) radiography for detection, classification, and measurement of peri-implant bone defects in an animal model. Methods Fifty-four mandible blocks with implants were harvested from nine male health adult beagle dogs with acquisition of IO, CBCT and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 43 publications
0
29
0
3
Order By: Relevance
“…Cone-beam computed tomography (CBCT) is helpful when assessing the peri-implant bone loss since it can provide a threedimensional relationship between a dental implant and the surrounding alveolar bone. Some previous studies have sought to identify bone conditions around implants using periapical radiographs and CBCT images together [38,39], and other studies have reported that CBCT has a high accuracy for detecting peri-implant bone defects [40,41]. Thus, it will be more meaningful if a machine learning system can utilize the information from the CBCT as well as two-dimensional radiographs when evaluating the peri-implant bone conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Cone-beam computed tomography (CBCT) is helpful when assessing the peri-implant bone loss since it can provide a threedimensional relationship between a dental implant and the surrounding alveolar bone. Some previous studies have sought to identify bone conditions around implants using periapical radiographs and CBCT images together [38,39], and other studies have reported that CBCT has a high accuracy for detecting peri-implant bone defects [40,41]. Thus, it will be more meaningful if a machine learning system can utilize the information from the CBCT as well as two-dimensional radiographs when evaluating the peri-implant bone conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the undeniable advantages of the aforementioned two-dimensional (2D) imaging modalities, they do not allow the assessment of the buccal bone, which is crucial for successful implant treatment. It is possible to evaluate the buccal bone level and its thickness by bone sounding using a periodontal probe, which is an invasive procedure, as well as ultrasonography and cone beam computed tomography (CBCT), which is a three-dimensional (3D), non-invasive imaging modality [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies recommend the use of CBCT for early evaluation of periodontal bone defects. However, due to artifact formation around dental implants, few studies recommend CBCT for bone assessment around dental implants [12][13][14][15][16][17]. Contemporary recommendations for the clinical use of CBCT in implant dentistry developed by indicate that although intraoral radiographs are still considered to be the primary tool for postoperative implant monitoring, we should realize that we need to evaluate threedimensional bone healing, including morphological, volumetric, and trabecular remodelling [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the use of CBCT results in exposure of higher radiation levels to patients than that of intra‐oral radiographs (Kadesjö et al, 2018 ). In addition, analyses of data from pre‐clinical studies have revealed conflicting results on the accuracy of assessments of bone levels when comparing intra‐oral radiographs, CBCT and histology (Corpas et al, 2011 ; Ritter et al, 2014 ; Song et al, 2021 ; Stokholm et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%